Theoretical methods for calculations of optical phonons in BiOBr: Analysis and correction of propagated errors - Ferrer, Mateus M. [UNESP]; Rodrigues, João Elias F.S.; Almeida, Marcio A.P.; Moura, Francisco; Longo, Elson [UNESP]; Pizani, Paulo S.; Sambrano, Julio R. [UNESP] (Wiley, 2018)
Theoretical and experimental methods were employed to investigate the vibrational modes of BiOBr. Wavenumber prediction and assignments of the infrared and Raman modes were performed using density functional theory and lattice dynamics calculations. The theoretical models were directly compared with the experimental results of particles fabricated using the microwave-assisted hydrothermal method and results reported in literature. The simulation results of the structure parameters, band gap, and vibrational modes are in agreement with the corresponding experimental values. The proposed models and calculations provided detailed insights into the vibrational modes and enabled to determine propagated assignment errors in results reported in the literature.
Keywords: BiOBr; density functional theory; GF-matrix; lattice dynamics calculation